Pemberdayaan UMKM Tape Melalui Pengolahan Limbah Kulit Singkong untuk Mendukung Sustainable Business di Desa Tegalwaru, Kabupaten Jember: Indonesia - Fatya, Adrin Putri; Ambarwati, Septiani Tri; Aji, Galih Setiyo; Khomariah, Feby Dea Nur; Suryono, M. Iqbal Krisna Hadi; Amalia, Dita; Windari, Riski Ayu; Sabilillah, Vanya Yuni Artafirdaus; Safitri, Erna Indah Dwi; Maharani, Sherly Apta; Sari, Vega Kartika (Universitas Mataram, 2025)
The MSME empowerment program in Tegalwaru Village, Jember Regency, aims to address the issue of cassava peel waste generated from tape production. Improperly managed cassava peel waste causes environmental pollution and potential health problems. Through this program, innovations were made to process cassava peel waste into solid and liquid organic fertilizers using bioreactors. The program involved training, material provision, and mentoring for MSME tape producers in the village. As a result, the use of organic fertilizer from cassava peel waste successfully reduced pollution and increased agricultural productivity. In addition to having a positive environmental impact, the program also created new economic opportunities and supported the concept of sustainable business in the village. The program’s sustainability is maintained through regular monitoring, both directly and via digital media.